The prevalence of COPD co-morbidities in Serbia: results of a national survey - Nagorni-Obradovic, Ljudmila M (NPJ Prim Care Respir Med, 2014)
BACKGROUND: Research studies have found different prevalence rates for co-morbidities in patients with chronic obstructive pulmonary disease (COPD). AIMS: The aim of our study was to investigate the prevalence of co-morbidities as well as functional limitations in subjects with COPD. METHODS: The study was based on a nationally representative sample of the population of Serbia. Information on the health of the population was obtained from interviews and anthropometric measurements. In this study we analysed a total of 10,013 respondents aged 40 years or older. There were 653 subjects with COPD and 9,360 respondents without COPD. RESULTS: Out of the 10,013 respondents, 5,377 were aged 40–59 years and 4,636 were 60 years or older. The prevalence of COPD was 5.0% in respondents aged 40–59 years and 8.3% in those aged 60 years or older; the total prevalence was 6.5%. The most prevalent co-morbidities among respondents with COPD were hypertension (54.5%) and dyslipidaemia (26.5%). The prevalence of all analysed co-morbidities was higher in respondents with COPD and the difference was highly statistically significant, except for stroke and malignancies, for which the difference was significant. Analysis showed that respondents with COPD had a higher prevalence of all analysed clinical factors (dizziness, obesity, anaemia and frailty) and functional impairments (mobility and hearing and visual impairment) compared with respondents without COPD. For those aged 40–59 years the difference was highest for mobility difficulty (four times higher prevalence in COPD patients) and anaemia (three times higher in COPD patients). CONCLUSION: Our analysis showed that the most prevalent co-morbidities in COPD were hypertension, dyslipidaemia, chronic renal disease and anxiety/depression. The finding suggests that health professionals should actively assess co-morbidities in patients with COPD.